2020
DOI: 10.1016/j.foodhyd.2020.105957
|View full text |Cite
|
Sign up to set email alerts
|

Starch replacement in gluten free bread by cellulose and fibrillated cellulose

Abstract: Highlights: The incorporation of (fibrillated) cellulose strengthened gluten free doughs  The generalised Maxwell model was applied to analyse dough rheology  The incorporation of (fibrillated)cellulose influenced the later stage of proofing  Volume and water competition dominates the thermal rheological behaviours  Loaves with (fibrillated)cellulose were smaller with harder, denser but finer crumb

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 65 publications
1
30
0
Order By: Relevance
“…Rice flour (11.08% moisture, 7.23% protein, 0.42% ash, 2.8% lipid, and 28.8% amylose as measured in a previous study 28 ) was purchased from Doves Farm. Allinson Easy Bake Yeast, sugar, sunflower oil, and salt were purchased from local supermarkets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rice flour (11.08% moisture, 7.23% protein, 0.42% ash, 2.8% lipid, and 28.8% amylose as measured in a previous study 28 ) was purchased from Doves Farm. Allinson Easy Bake Yeast, sugar, sunflower oil, and salt were purchased from local supermarkets.…”
Section: Methodsmentioning
confidence: 99%
“…Methylcellulose (Methocel® A4M) were purchased from The DOW Chemical Company (Bomlitz, Germany). Psyllium seed husk powder (Vitacel®) (7.23% moisture, 3.40% protein, 2.89% ash, and 3.30% lipid as measured in a previous study 28 ) was kindly donated by the JRS (J. Rettenmaier & Söhne Group, Rosenberg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…These observations suggest that the incorporation of djulis in the sourdough bread may reduce the loaf rising. Similarly, previous studies showed that change in the formulation may affect the loaf volume [28,29]. Such changes could be related to several parameters including the effect of the formulation on the gluten network as well as on the fermentation process.…”
Section: Appearance and Bread Volumementioning
confidence: 66%
“…The results of the present study were in line with those reported in the literature. For example, researchers observed a notable impact of formulation on the textural attributes of bread [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation